Tunable surface plasma resonance of gold nanorods superstructure and their SERS properties. (1st September 2018) - Sun, Yufei; Wang, Liwei; Liu, Junhui; Li, Ruoping; Huang, Mingju
Abstract : High‐quality gold nanorods (GNRs) with different aspect ratios and uniform morphology were synthesised using the seed‐mediated growth method. The GNRs were assembled into two different type superstructures: the one is arranged vertically to the substrate (V‐GNR superstructure); the other is arranged parallel to the substrate (P‐GNR superstructure). Their work at present is devoted to study the Raman enhancement effect and signal repeatability of GNR superstructures. The influence of GNRs arrangement on surface‐enhanced Raman scattering (SERS) was investigated experimentally. In addition, the electromagnetic field coupling of GNR superstructures with different arrangement modes was simulated by the finite‐different time‐domain method. Both experiments and theories have proved that the required resonance wavelength of Raman laser can be obtained by adjusting the aspect ratio of GNRs. Furthermore, the P‐GNR superstructure can bring high and repeatable SERS signal intensity of molecules compared with V‐GNR superstructure and other nanostructures. It can be concluded that P‐GNR superstructure is a good substrate mode for SERS technique.